Regional patterning of funerary pottery in Pannonia - Krekovič, Eduard (Rei Cretariae Romanae Fautorum Acta, 2022)
The author examines differences in the deposition of pottery into graves in various regions of Pannonia in the first three centuries AD. – Pannonia Superior: Carnuntum – although the location of the legionary fortress, the examined material originates from the cemetery to the south of the civilian town; Gerulata – an auxiliary fort (Cemetery II); Poetovio – a civilian town (the northern cemetery). – Pannonia Inferior: Aquincum – the cemetery located west of the canabae; Matrica – an auxiliary fort. Based on their functionality the author devised seven categories (jugs, beakers, plates, pots, bowls, cups, and censers) and an additional two categories representing terra sigillata and lamps. Within these indexes differences existed at both cemeteries and in the regions. Some of these can be explained, but some remain unexplained. It is possible that some differences could be dependent on the ethnicity of the deceased. For the most part the differences concern the numbers and combinations of particular shapes of the vessels. On the other hand, the overall trends in deposition of the vessels at all cemeteries can be observed. The preference for vessels for the purpose of drinking is one of these. This mostly concerns their total numbers, and also the combination of a jug and beaker. It seems that for the Romans it was more important to supply their deceased with drinks rather than with food.